The impact of the liberalization of public services on the competitiveness of firms in the Alpine regions of Switzerland - Alain Thierstein; Christof Abegg (European Regional Science Association (ERSA), 2002)
Businesses in outlying regions, particularly small and medium-sized enterprises (SMEs), are having to face a broad range of different challenges in order to maintain their competitiveness. An important input factor has in the past always been the supply of public services. In recent years, public services have undergone a number of radical changes. This paper works on the hypotheses that the market-oriented reorganisation of capacity in the supply of public services has affected outlying regions more than urban centres and led to an increase in economic concentration and regional disparities. The paper has the following objectives: (1) to look at the interconnections between the different aspects of change in the supply of public services and the development of business; (2) to outline the empirical design for analysing the relative significance of supply of services as a dynamic locational factor for businesses in the Swiss Alpine regions. This paper will draw from an ongoing empirical study, but cannot yet indicate policy implications. We will argue that the companies based in outlying regions are affected in two respects by the reduction in public services. On the one hand, the changed provision of public services is becoming more significant for businesses as a hard locational factor and can have a negative effect on production processes. The main analytical approach to assess firms behaviour within a regional context is the concept of 'regional production systems' (RPS). RPS are characterised by their scope for autonomous decision-making, their coordination mechanisms and their specific resources. The extent to which they are anchored in their particular region influences their capacity for innovation and adaptation to a changing economic context. Thus companies are being forced to react to the dynamic environment and to develop - probably in cooperation with regional public bodies - corresponding response strategies. On the other hand, public services work as soft, person-centred, locational factors that make a major contribution to the quality of life a location has to offer. An deterioration in services means that outlying regions become less attractive as a place to live and consequently it becomes more difficult for companies based there to recruit well-qualified employees. Companies are being forced to react to the dynamic environment and to develop corresponding response strategies.
Keywords: 330